BRIDGING BORDERS, PROTECTING RIGHTS: EVALUATING INDONESIA’S MIXED MARRIAGE POLICY FOR CITIZENS IN CHINA: Received: 24th September 2025, Revised: 27th October 2025, 30th October 2025, Accepted: 10st November 2025, Date of Publication: 04th December 2025 - Indah,; Pardamean Daulay,; Abdul Rahman, (PEOPLE: International Journal of Social Sciences, 2025)
This study examines the implementation of Indonesia’s Mixed Marriage policy for Indonesian citizens residing in China. The rising number of mixed marriages between Indonesian women and Chinese men has brought about legal and social challenges, including cases of exploitation, human trafficking, and unclear legal status. A notable phenomenon is the emergence of informal Mail Order Bride arrangements, where Indonesian women relate to foreign spouses through unregulated networks and digital platforms, often bypassing official procedures and facing significant risks. Using a qualitative descriptive approach, the research analyses the effectiveness of existing policies, identifies structural, legal, and social barriers, and evaluates the roles of both Indonesian and Chinese authorities in safeguarding citizens’ rights. Data was collected through interviews, document analysis, and field observations. Findings reveal that weak inter-agency coordination, limited institutional capacity, and unclear bureaucratic procedures hinder effective policy implementation. These gaps leave Indonesian citizens vulnerable to rights violations and legal insecurity. The study recommends strengthening bilateral legal frameworks, providing pre-marital legal education for prospective spouses, and establishing joint verification and protection mechanisms to ensure the dignity, safety, and legal certainty of Indonesian citizens in transnational marriages. This study investigates how Indonesia’s policies on mixed marriages are implemented for its citizens living in China. The increasing trend of marriages between Indonesian women and Chinese men has triggered a range of legal and social issues, including exploitation, human trafficking, and ambiguous legal standing. A particularly concerning development is the rise of informal “mail-order bride” arrangements, wherein Indonesian women connect with Chinese partners via unregulated digital channels and informal networks—often circumventing official legal processes and exposing themselves to serious risks. Adopting a qualitative descriptive methodology, the research evaluates the efficacy of current policies, pinpoints structural, legal, and societal obstacles, and assesses the roles played by both Indonesian and Chinese governmental bodies in protecting their citizens’ rights. Data was gathered through in-depth interviews with embassy staff, analysis of official documents, and on-site fieldwork. The findings indicate that ineffective coordination among government agencies, insufficient institutional resources, and vague bureaucratic protocols significantly impede policy enforcement. These systemic shortcomings leave Indonesian nationals—particularly women—in vulnerable positions, susceptible to rights abuses and legal uncertainty. To address these challenges, the study proposes several key interventions: reinforcing bilateral legal agreements between Indonesia and China, instituting mandatory pre-marital legal education for couples entering transnational unions, and creating joint verification and protection systems. These measures aim to uphold the dignity, safety, and legal security of Indonesian citizens involved in cross-border marriages.